Determinants of Islamic and conventional banks profitability in Malaysia - Nashita Hani, Ruslan (2015)
This study investigates the determinants of Islamic and conventional banks profitability of 30Malaysian commercial banks over the period from 2007 to 2012. Using the Ordinary Least Square (OLS), the result shows that capital significantly influences the return on assets (ROA) of Islamic and conventional banks in Malaysia. This implies that strong capital base is important in determining the profitability of commercial banks in Malaysia. For macroeconomic variables, inflation determines the profitability of Malaysian conventional banks only but not Islamic banks. As for the interest rate, which is measured by base lending rate (BLR), the findings demonstrate that BLR positively and significantly influences the ROA of the full sample. This study also controls for the effect of 2008 global financial crisis on the profitability of Malaysian commercial banks by introducing CRISIS dummy in the model. The result indicates that Malaysian bank profitability is not affected by the 2008 global financial crisis